Influence of Psychological Nursing Procedure on Negative Emotion, Stress State, Quality of Life and Nursing Satisfaction in Patients with Lung Cancer Radical Operation - Yu, Yizhi; Xia, You; Fan, Xiaoyan; Chen, Yong; Li, Chengjuan; Zhang, Jing (Frontiers in Surgery, 2022)
Objective:To discuss the influence of psychological nursing procedure on negative emotion, stress state, quality of life and nursing satisfaction in patients with lung cancer radical operation. Methods:106 patients with lung cancer who underwent radical resection in our hospital from September 2019 to September 2021 were selected. According to the intervention time, patients were divided into group A and group B, with 53 cases in each group. Group A received routine nursing, group B used psychological nursing procedure on the basis of group A. The negative emotions, stress state, quality of life and nursing satisfaction of patient were observed. Results:Self-rating Anxiety Scale and Self-rating Depression Scale scores of Group B were lower than Group A (P<0.05). The levels of norepinephrine, epinephrine and cortisol in Group B were lower than Group A (P<0.05). Generic Quality of Life Inventory-74 scores of Group B were higher than Group A (P<0.05). The nursing satisfaction of Group B (88.68%) was higher than Group A(73.58%) (P<0.05). Conclusion:Psychological nursing procedure is conducive to reducing the negative emotion, relieving stress reaction, improving the quality of life, increasing nursing satisfaction of patients with lung cancer radical operation.